2013
DOI: 10.3325/cmj.2013.54.180
|View full text |Cite
|
Sign up to set email alerts
|

Arterial blood architecture of the maxillary sinus in dentate specimens

Abstract: AimTo describe vascular anatomy of the maxillary sinus in dentate specimens dissected from human cadavers.MethodsTwenty dentate maxillary specimens were dissected, anatomically prepared, and injected with liquid latex for a better visualization of the maxillary sinus artery.ResultsWe found an intraosseous anastomosis in 100% and an extraosseous anastomosis in 90% of the cases. The anterior lateral wall of the maxillary sinus was transversed by two anastomoses between the posterior superior alveolar artery (PSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 10 publications
4
30
0
3
Order By: Relevance
“…25 Another study, aiming to identify the branches of the maxillary artery, did not provide information on the prevalence within the sinus lateral bony wall. 26 One more report was discarded because it reported surgical information from a series of cadaveric material, 13 and five articles describing a prevalence of 100% of PSAA within the sinus wall, based on anatomical dissections, were also excluded from this metaanalysis 6,7,11,25,27 (Table 1). Finally, another paper was discarded because CT scans were performed to investigate sinus disorders.…”
Section: Resultsmentioning
confidence: 99%
“…25 Another study, aiming to identify the branches of the maxillary artery, did not provide information on the prevalence within the sinus lateral bony wall. 26 One more report was discarded because it reported surgical information from a series of cadaveric material, 13 and five articles describing a prevalence of 100% of PSAA within the sinus wall, based on anatomical dissections, were also excluded from this metaanalysis 6,7,11,25,27 (Table 1). Finally, another paper was discarded because CT scans were performed to investigate sinus disorders.…”
Section: Resultsmentioning
confidence: 99%
“…The middle superior alveolar artery branches from the infraorbital artery and runs inferiorly along the lateral wall of the maxillary sinus toward the region of the canine and lateral incisor teeth and anastomoses with the anterior and posterior superior alveolar arteries (Standring, ). Although previous studies have reported an anastomosis between the posterior superior alveolar artery and infraorbital artery (Solar et al, ; Traxler et al, ; Kqiku et al, ), variations in maxillary sinus vascular connections (Ella et al, ; Sato et al, ), and the prevalence, diameter, and location of the posterior superior alveolar artery and its relationship with the alveolar ridge (Elian et al, ; Guncu et al, ; Jung et al, ; Ilguy et al, ), these studies have primarily focused on the vascular injury during sinus floor augmentation and have failed to clarify the topographical relationships between the superior alveolar arteries and the maxillary sinus.…”
mentioning
confidence: 99%
“…Maksiller kemiğin nekrozu ve kanama komplikasyonlarını önlemek amacıyla cerrahi tedaviler (osteotomi, endodontik cerrahi, dental implant, yaralanma tedavileri) sırasında maksiller sinüsün vaskülarizasyonu, PSAA'nın alveolar kemikten vertikal yüksekliği ve maksiller dişlerle seviyesi hakkında bilgiye sahip olmak önemlidir. 56,57 PSAA ve IOA'nın maksimum çapı 2 mm ile 2,7 mm arasındadır. Büyük çaplı arterler daha fazla kanama problemine yol açacağından sinüs ogmentasyonunda dikkatli olunmalıdır.…”
Section: Görüntü Kalitesiunclassified